The analysis of health problem on worker from different field activities in oil palm plantation / Muhammad Akmal Syakir Kamal Ruzzaman - Kamal Ruzzaman, Muhammad Akmal Syakir (Faculty of Plantation and Agrotechnology, 2019)
Oil palm task activities is the most important factors that lead the estates or farm into the profitability and productivity. Therefore, there are important for oil palm workers to know what health problem or risk that might be occur in oil palm occupation. The health risk on workers can affect the productivity of oil palm. The aim of this research study is to identify the health problem arise from the field activities, to determine which activities can contribute to the high health problem and to investigate the impact of health problem with worker productivity. The research was conducted at Ladang Sri Keruing with the total respondent 86 out of 110 populations. The data were analyses by descriptive analysis, correlation and regression analysis by using the Statistical Package for Science Social (SPSS) version 25. The result shows that all independent variable which is physical accidents, mental health problem, injuries or disease detected and short-term and long-term effect have weak relationship with workers productivity, relationship still p-value is less than 0.05. In addition, research study also found that a lot health risk that might be occur in oil palm occupation. As a conclusion, the most effective factor contribute to the low productivity is the injuries and diseases detected in estates.